Application of nano-TiO@adsorbent composites in the treatment of dye wastewater: A review - Jing Guo; Tingting Zhou; Hong Guo; Chao Ge; Jianjun Lu (Journal of Engineered Fibers and Fabrics)
A large amount of wastewater with a high dye content is discharged from the textile printing and dyeing industry. Synthetic dyes, which are essentially exogenous chemicals, predominantly exhibit the property of poor biodegradability. Consequently, they are capable of persisting stably within the environment over protracted time spans. The high-chroma dye wastewater not only results in severe water pollution but also breaks ecological balance, thereby rendering it a pivotal and formidable facet in the realm of industrial wastewater treatment. Consequently, the treatment of printing and dyeing wastewater prior to its discharge is of utmost necessity. This article offers a relatively comprehensive exposition of the treatment methods for dye wastewater, with a specific focus on the adsorption method, the photocatalysis method, and their respective characteristics. Nano-TiO 2 @adsorbent composites, which integrate the advantages of adsorption and photocatalysis, have been widely studied for the treatment of dye wastewater. This paper provides a broad overview of the classifications, the adsorption-photocatalytic mechanism, and influencing factors of nano-TiO 2 @adsorbent composites. Nano-TiO 2 @adsorbent composites integrate the processes of adsorption, catalysis, and degradation, thereby significantly improving the efficiency of photocatalytic degradation for organic pollutants by titanium dioxide catalysts. Furthermore, the suggestion for the research and development of photocatalyst @textile composite materials for dye wastewater treatment is put forward in this article.